"Cheap Talk" in International Trade Law. (8th April 2022) - Park, Tae Jung
Abstract: There is a dilemma in the field of international trade law: Many negotiating countries fail to complete treaties during the renegotiation period. 1 Due to tight schedules in the primary negotiation, the parties normally insert a renegotiation clause to postpone completion of a treaty. However, the parties frequently postpone the completion of the treaty even in the renegotiation phase. The literature has neglected to consider the existence and causes of these issues, as well as the solutions to them. This article aims to remedy this neglect.